MULTIPLE REGRESSION : DETEMINANT ON PROFITABILITY AT ISLAMIC COMMERCIAL BANKS IN INDONESIA - Tisna Amijaya, Dodi; Siti Komariah (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The Islamic financial system is potential to be a locomotive of the national economy and be able to overcome gaps. One of them is Islamic banking which is increasingly developing in Indonesia. The development of Islamic banking is expected to increase economic growth. For this reason, Islamic banking is needed which has a healthy financial performance. This study aims to analyze the effect of NPF, CAR, and FDR on Profitability at Islamic Commercial Banks. The data used in this study were obtained from Islamic commercial bank financial statements which are recorded in the OJK for 2015-2018. The population in this study is 14 Sharia Commercial Banks in Indonesia, and using the purposive sampling method, there are 12 bank samples which will be examined. The analysis technique used in this study is multiple linear regression models. The results showed that NPF, CAR and FDR had a significant effect on profitability.